A novel mutation KCNJ11 R136C caused KCNJ11-MODY - Yaning Chen; Xiaodong Hu; Jia Cui; Mingwei Zhao; Hebin Yao (Diabetology & Metabolic Syndrome, 2021)
Abstract A young female patient, diagnosed with diabetes mellitus at the age of 28 years old in 2009, carries KCNJ11 R136C by whole exome sequencing and her daughter doesn’t carry this mutation. Bioinformatics software predicted that the 136th amino acid is highly conservative and the mutation is deleterious. KCNJ11 R136C can result in the change of channel port structure of KATP channel. So she was diagnosed as KCNJ11-MODY.